Phase equilibria and thermodynamic evaluation of the Fe-V-O system in air. (December 2018) - Malan, Willem Dutoit; Akdogan, Guven; Taskinen, Pekka; Hamuyuni, Joseph; Zietsman, Johan
Abstract: The Fe-V-O system in air was studied experimentally ranging from 700 °C to 1450 °C by high-temperature equilibration, quenching, scanning electron microscope and microprobe analysis. The thermodynamic evaluation was performed with FactSage 7.0. The solubility of V2 O5 (s) in Fe2 O3 (s) was described with the compound energy formalism. The properties of the liquid phase were described with both the quasichemical model and the associate species model. A set of self-consistent thermodynamic parameters were estimated within acceptable error limits. The calculated phase diagram of Fe-V-O in air is presented and compared to experimental observations and other literature data.